Pengaruh Perputaran Piutang dan Perputaran Modal Kerja Terhadap Profitabilitas Pada CV. Gadjah Bordir - Gini Gini; Sjamsul Hidayat; Fitri Nuraini (SUSTAINABLE JURNAL AKUNTANSI, 2022)
Amid the intense business competition companies are required to be able to achieve market positions, so companies need to carry out credit sales strategies, so that sales increase. In CV Gadjah of Embroidery is a business activity. Gadjah of Embroidery requires a big cost because in the process of work, it requires costs and energy for its production. The So financial problems become a burden on CV. Gadjah of Embroidery business. The CV. Gadjah of Embroidery because its can be an obstacle to the cost of production.The purpose of the study was to determine the effect of accounts receivable and working capital turnover on profitability at CV.Gadjah of Embroidery for the period 2015-2020.The method of this study uses quantitative methods to measure the influence of accounts receivable and working capital turnover of profitability in CV. Gadjah of Embroidery, the observation period in 2015 - 2020. Hypothesis testing is using descriptive analysis method, statistical analysis method consisting of multiple linear regression analysis Simultaneous significant testing (F test), partial significance testing (Test-T) and Determination Coefficient Testing (R2). The results showed that there was an influence on the rotation of accounts on profitability in CV. Gadjah of Embroidery, while working capital turnover was an influence on profitability in CV.Gadjah of Embroidery. The Adjusted R square value = 0.666 means 66.6 percent of the influence of accounts receivable and working capital on profitability on CV. Gadjah of Embroidery. While the remaining 33.4 percent explained by other variables outside the variables used in this study.